Promoting participation in oilseed value chains in Malawi: Who and where to target - Benson, Todd (International Food Policy Research Institute, 2020)
By increasing their production for the market and realizing greater incomes, smallholder farming households can significantly accelerate local agricultural and rural economic development. The increased income of these commercially oriented farmers increases their demand for the goods, services, and labor that can be supplied by other, often poorer, households in their community, expanding local non-farm employment opportunities and raising incomes for those other households. Appropriately targeting agricultural development efforts towards commercially oriented farming households has important second-round economic development benefits in their communities, effects which cannot be achieved without properly identifying such households. In this Policy Note, we examine both household and spatial factors that may drive participation by smallholder farming households in oilseed value chains, focusing on those for groundnut, soyabean, and sunflower. Groundnut has been an important secondary crop within many smallholder farming systems across Malawi for several generations, used both for own consumption within the household and for sale. Soyabean and sunflower are more recent introductions and are primarily grown for commercial sale by both smallholders and commercial farmers. Annual production and yield levels for these crops in recent years are shown in Table 1.